2012
DOI: 10.1002/mrm.24194
|View full text |Cite
|
Sign up to set email alerts
|

White matter and deep gray matter hemodynamic changes in multiple sclerosis patients with clinically isolated syndrome

Abstract: The dynamic susceptibility contrast magnetic resonance imaging perfusion technique was used to investigate possible hemodynamic changes in normal appearing white matter and deep gray matter (DGM) of 30 patients with clinically isolated syndrome (CIS) and 30 patients with relapsing-remitting multiple sclerosis. Thirty normal volunteers were studied as controls. Cerebral blood volume, cerebral blood flow (CBF), and mean transit time values were estimated. Normalization was achieved for each subject with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 57 publications
6
37
0
1
Order By: Relevance
“…Such lesions were detected only in 5% of our patients with primary NPSLE. Inflammatory activity has been related to increased perfusion due to inflammation-mediated vasodilation 44. Our findings of diffuse hypoperfusion, along with the rarity of inflammatory-like lesions on conventional MRI, suggest that in most cases primary NPSLE is characterised by chronic widespread decreased perfusion and ischaemia due to microvasculopathy and subsequent neuronal loss in the absence of high-grade inflammation.…”
Section: Discussionmentioning
confidence: 61%
“…Such lesions were detected only in 5% of our patients with primary NPSLE. Inflammatory activity has been related to increased perfusion due to inflammation-mediated vasodilation 44. Our findings of diffuse hypoperfusion, along with the rarity of inflammatory-like lesions on conventional MRI, suggest that in most cases primary NPSLE is characterised by chronic widespread decreased perfusion and ischaemia due to microvasculopathy and subsequent neuronal loss in the absence of high-grade inflammation.…”
Section: Discussionmentioning
confidence: 61%
“…Perfusion studies based on multiple imaging modalities reported reduced cerebral blood flow (CBF) in MS. 45 In some patients, new focal lesions were observed with reduced mean diffusivity (MD) on diffusion MRI, similar to that observed in acute ischemic lesions. 6–8 To better explain aspects of the observed pathological features of MS it was postulated that hypoperfusion plays a critical role in the pathogenesis of MS. 9 …”
Section: Introductionmentioning
confidence: 71%
“…[16][17][18] Similar observations were made in the deep gray matter of clinically isolated syndromes suggestive for MS and relapsing-remitting MS patients. 19 These results suggest that cerebral hypoperfusion, regardless of the clinical subtype, is an early and integral part of MS pathology.…”
Section: Introductionmentioning
confidence: 95%